Dominant carrier market power in US international telephone markets - Alleman, J.; Madden, Gary; Savage, Scott (Routledge, 2003)
An econometric model is used to examine market power in US international telephone markets. Lerner index estimates suggest AT&T's collection rate-cost margin was between 12% and 24% during 1991 to 1995. Although Lerner estimates imply deadweight welfare losses of up to US $261 million per annum, such losses are small compared to those from the inefficient pricing of international interconnection. Settlement rate-cost margins on US bilateral markets of approximately 89% translate into a US $4907 million transfer from consumers to carriers in 1995.